Mineral and Vitamin B Contents of Sapudi and Merino-cross Meat - Himmatul Khasanah; Desy Cahya Widianingrum; Nurul Pratiwi (Institut Pertanian Bogor, 2025)
Lamb is important in providing balanced and healthy nutrition as a source of protein, fat, and essential micronutrients such as iron, zinc, and vitamin B complex. The mineral and vitamin content of meat from local breeds needs to be evaluated as a portrait of the genetic quality data of sheep and as a reference for developing sheep that produce healthy and high-quality meat. This study aimed to analyze the mineral and vitamin B contents of Sapudi sheep and Merino cross sheep meat from the longissimus dorsi area to invent genetic quality data for the meat of these two sheep. Three Sapudi and three Merino cross sheep were kept under similar conditions for two months. Meat collection from the longissimus dorsi muscle was carried out to analyze vitamin B and mineral content. A t-test was then performed to determine meat quality. The results showed that the mineral content of Mn and Cu in Sapudi sheep meat was lower than that in Merino cross meat. The vitamin B2 content in Sapudi sheep (0.11 mg/100 g) is lower than that of Merino cross (0.20 mg/100 g). In comparison, the vitamin B3 content of Sapudi sheep meat was higher (0.51 mg/100 g) than Cross-merino (0.40 mg/100 g). This research concludes that breeding influences nutrient content, and Merino crossbreed sheep are superior to Sapudi sheep in terms of vitamin B and mineral content. Keywords: genetic resource, Indonesian local lamb, meat quality, mineral, vitamin